Assessment of role of green bond in renewable energy resource development in Japan. (January 2023) - Taghizadeh-Hesary, Farhad; Phoumin, Han; Rasoulinezhad, Ehsan
Abstract: The main purpose of this research is to investigate the effects of issued green bonds and energy price volatility on the consumption of three types of green energy (wind, solar, and hydro) in Japan during 1990–2020. For this purpose, an autoregressive distributed lag (ARDL) estimation method was used. The main findings revealed the long-term positive impacts of issued green bonds and energy prices and the negative impact of geopolitical risk on the wind energy consumption. In contrast, geopolitical risk and energy prices have no significant short-term impacts on solar energy consumption in Japan. Solar energy and hydro energy experienced the most considerable impact from issuance of green bonds in Japan. Moreover, a unidirectional causal relationship runs from green bonds and geopolitical risk to wind, solar, and hydro-energy consumption. At the same time, a bidirectional linkage exists between energy prices and green energy (solar, wind, and hydro) consumption in Japan. As practical policies, Japan should try to develop green bond market and promote digital green financing tools that are more resilient and adaptable to the post–COVID-19 era. Highlights: We investigate the impact of green bonds on three types of clean energy (solar, wind, hydro) in Japan. Green bonds and energy prices have a long-term positive impact on wind energy consumption. Solar energy and hydro energy experienced the most considerable impact from the issuance of green bonds in Japan. Japan should try to develop green bonds market and establish digital green financing tools.